Syphilis in Swaziland: a serological survey. Issue 2 (April 1981) - Ursi, J P; van Dyck, E; van Houtte, C; Piot, P; Colaert, J; Dlamini, M; Meheus, A
Abstract : Sera from 536 adults and children in Swaziland were examined for their reactivity in the rapid plasma reagin (RPR) and Treponema pallidum haemagglutination (TPHA) tests. None of 130 sera from children was reactive in either test; 8.6% of sera from 185 healthy adults were reactive in the RPR test and 33% in the TPHA test; 24.5% of 220 sera from patients with genital ulcers were RPR-positive and 45.9% TPHA-positive. The RPR positivity rates were not related to age, but the percentage of RPR-negative, TPHA-positive sera increased with age in both the healthy adults and the patients with genital ulcers. Thus venereal syphilis appears to be responsible for these high positivity rates. Estimates of the yearly incidence of syphilis are identical for both groups--approximately 1.4%, an unusually high figure.